Sudden Cardiac Death in Children Affected by Cardiomyopathies: An Update on Risk Factors and Indications at Transvenous or Subcutaneous Implantable Defibrillators - Rella, Valeria; Parati, Gianfranco; Crotti, Lia (Frontiers in Pediatrics, 2020)
In the present paper, we will discuss the main cardiomyopathies affecting children with a specific focus on risk stratification and prevention of sudden cardiac death (SCD). We will discuss the main clinical features of hypertrophic cardiomyopathy (HCM), dilated and restrictive cardiomyopathies, left ventricular non compaction (LVNC) and arrhythmogenic cardiomyopathy (AC), always highlighting their peculiarities in the pediatric age. Since sudden cardiac death may be the first manifestation of the disease, even in children, the identification of the specific underlying condition and of risk factors are pivotal to carry out the appropriate preventing strategies. ICD recommendations in children are similar to adults, but supporting evidences are not so solid, being based on registries or single center studies. Furthermore, children and young patients are most likely to manifest long term complications related to an implanted ICD, and this should be taken into account when evaluating the risk benefit ratio. In this perspective, subcutaneous ICDs (S-ICDs) could carry an advantage; however, they cannot be considered in small children for technical reasons. Data on effectiveness and safety of S-ICDs in a pediatric population is still lacking, although some limited experiences are reported and will be discussed in the current review.